Parental and Child Self‐Efficacy Explaining Food Intake through Self‐Regulation: A Dyadic Prospective Study. Issue 1 (13th September 2020) - Zarychta, Karolina; Banik, Anna; Kulis, Ewa; Lobczowska, Karolina
Abstract : Background: According to social cognitive theory and socio‐ecological models, self‐efficacy and temptation‐related self‐regulation (the use of distraction or suppression) are modifiable predictors of health behaviors, such as food intake. Yet, there is limited evidence explaining how these factors are interlinked among parent‐child dyads. This study investigated indirect effects of parental and child self‐efficacy on food intake, via parental and child self‐regulation. Methods: The prospective study (the baseline [T1] and the 10‐month follow‐up [T2]) enrolled 924 parent‐child dyads (1, 848 individuals; 54.3% girls, aged 5–11 years, 88.9% mothers). Dyads were interviewed or completed self‐report measures. Path analyses with maximum likelihood estimation were conducted. Results: Child self‐efficacy and distraction (T1) mediated between parental self‐efficacy (T1) and higher levels of child fruit and vegetable intake (T2). No significant mediating effects of suppression were found, nor indirect effects of parental self‐efficacy (T1) on energy‐dense food intake (T2). Conclusion: Health promotion interventions aiming at changing fruit and vegetable intake among 5–11‐year‐old children should target enhancing parental and child self‐efficacy that may facilitate the use of self‐regulation and, in turn, healthy diet.